Povezanost med slogi navezanosti, prepričanostjo v obstoj Boga, duhovnostjo ter odnosom do slavnih pri mladih na prehodu v odraslost - Cugmas, Zlatka (Psihološka obzorja (Ljubljana), 2025)
Young people often develop close parasocial relationships, such as celebrity relationships. These relationships are one-sided, but often very intimate. In a research involving 182 young people aged 18 to 30, we examined how these relationships are related to their attachment style, belief in the existence of God, and spirituality. We expected that attachment style, belief in God, and spirituality significantly predict parasocial relationships. We translated and adapted the following rating scales for the research: Adolescent Romantic Parasocial Attachment, Celebrity attitudes, Relationship Scales Questionnaire, Existence of God Scale, and The New Age Orientation Scale. Among the attachment styles studied, only the preoccupied/ambivalent attachment style and the belief in the existence of God significantly positively predicted the romantic parasocial attachment of young people at the transition to adulthood and their attitudes towards celebrities. Higher levels of spirituality also significantly predicted romantic parasocial attachment, but not achievement on the scale of intense celebrity relationship. The results support the findings of previous studies on the association between attachment styles and parasocial relationships and extend them with findings related to belief in God and spirituality. There is a need for further development of instruments for the study of parasocial relationships and spirituality.
Keywords: attachment style; duhovnost; emerging adulthood; parasocial relationships; parasocialni odnosi; prehod v odraslost; religija; religion; spirituality; stili navezanosti